Evaluation of an Absorption Based aMDEA Process Using Aspen Plus: A conceptual study of biobased carbon capture technology for a combined heat and power plant - Larsson, Jesper; Larsson, Tove (My University, 2022)
Production of heat and power through combustion of fossil fuels has contributed with increased levels of CO2 in the atmosphere, causing climate change and environmental problems. A solution to contribute to a sustainable energy system and mitigate CO2 emissions, is to combine biomass gasification with carbon capture technology. This thesis aims to investigate a hydrogen production unit for a combined heat and power plant, which includes chemical absorption based carbon capture. The solvent used is an aqueous solution of N-Methyldiethanolamine (MDEA) and piperazine (PZ). Models for the hydrogen production process were constructed in the simulation software Aspen Plus. The carbon capture model was investigated in a parameter study where important process parameters were identified. Liquid-to-gas ratio, solvent composition, pressures levels in the absorption and desorption columns, and feed temperatures into the respective columns were investigated. An optimization with the objective of minimizing the heat demand in the process was also included in the model evaluation. Liquid-to-gas ratio was found to have a large impact on the absorption efficiency, with increased absorption as a result of increased liquid-to-gas ratio. It was found that an optimum ratio could be located, where excess heating of the process was kept to a minimum. Investigation of solvent composition showed that the ratio between MDEA and PZ was a key design parameter, in terms of carbon capture efficiency and energy demand of the process. An increase in capture rate as a result of increased pressure in the absorber was recognized, as a cause of increased solubility of CO2 at higher pressures. Increased pressure in the stripper column was identified as a parameter favorable for increased heat integration of the system.
Keywords: Aspen Plus; Carbon capture; Chemical absorption; MDEA; PZ